2020
DOI: 10.1007/s15010-020-01527-z
|View full text |Cite
|
Sign up to set email alerts
|

Hospital at home for the management of COVID-19: preliminary experience with 63 patients

Abstract: Alternatives to conventional hospitalization are needed to increase health systems resilience in the face of COVID-19 pandemic. Herein, we describe the characteristics and outcomes of 63 patients admitted to a single HaH during the peak of COVID-19 in Barcelona. Our results suggest that HaH seems to be a safe and efficacious alternative to conventional hospitalization for accurately selected patients with COVID-19. Keywords COVID-19 • Hospital at home • Alternative medical care facilities • Alternatives to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 7 publications
1
37
0
7
Order By: Relevance
“…Finally, HaH Units have played different roles during the COVID‐19 pandemic, but mostly provided first line care of COVID‐19 patients at their homes or in medicalized civil buildings such as hotels 11 . During this period, HaH units have accumulated a large amount of experience in dealing with COVID‐19 patients, the evolution of the disease and the criteria for HaH admission (Table 1) or conventional hospitalization transfer due to clinical worsening.…”
Section: Figurementioning
confidence: 99%
“…Finally, HaH Units have played different roles during the COVID‐19 pandemic, but mostly provided first line care of COVID‐19 patients at their homes or in medicalized civil buildings such as hotels 11 . During this period, HaH units have accumulated a large amount of experience in dealing with COVID‐19 patients, the evolution of the disease and the criteria for HaH admission (Table 1) or conventional hospitalization transfer due to clinical worsening.…”
Section: Figurementioning
confidence: 99%
“…This care model remains a viable solution to the increasing global need for acute care hospital beds, rising healthcare costs, and aging population 2 , 3 . While HaH is not novel, the emergence of the coronavirus disease 2019 (COVID-19) has brought new urgency to this mandate as the world grapples with the accelerating need for hospital beds and increased risk of nosocomial infections 4 . Studies have shown that HaH is a safe and effective alternative for COVID-19 patients with mild symptoms, which can reduce pressure on healthcare in the hospital 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The current COVID-19 pandemic is one of the greatest public health crises of our time (European Centre for Disease Prevention and Control, 2019;World Health Organization, 2020a), and has forced health systems worldwide to urgently find ways to relieve pressure on overstretched hospitals and increase bed availability. One outcome has been an increase in the use of HaH programmes, which have proven to be both an efficient and safe option for providing care to selected at-risk patients (Coloma and Nicolás, 2020;Moghadas et al, 2020;Pericàs et al, 2020;Shoukat et al, 2020). OPAT patients, for example, are a COVID-19 risk group because of their susceptibility to severe infections and extensive contact with the healthcare system (Mansour et al, 2020).…”
Section: Introductionmentioning
confidence: 99%